The Impact of Islamic Spiritual Leadership on Digital Public Relations Effectiveness - Maysa Bela, Nanda; Daryono (Inovasi Analisis Data, 2025)
Objective: The current study discusses the relationship between the Islamic spiritual leadership and the digital public relations effectiveness while proposing the spiritual-cultural fit as a critical mediator in the organizational contexts based on religion.Methods: This study uses a quantitative survey of communication professionals in organizations associated with Islam, and structural equation modeling for assessing associations between leadership dimensions and digital expression PR outcomes.Results: Islamic spiritual leadership is a fundamental factor in improving digital PR effectiveness, whereby the spiritual–cultural fit could act as a strong mediating variable. These dimensions of communal stewardship, propagation responsibility, eternal accountability, and consultative decision-making together as a part suggest that value congruence is a fundamental principle of digital engagement strategies expected to make a substantial contribution to the success of digital communication, indeed.Novelty: This paper presents a new concept, spiritual-cultural fit, into the public relations literature by integrating leadership theory and the strategic message effectiveness in the context of religion. It introduces a new approach where Western-oriented PR models are balanced and blended with Islamic spirituality into a social media framework.Research Implication: This study lays the groundwork for Islamic Public Relations Theory development and practical guidance for faith-driven organizations experiencing digital transformation. It illustrates how, rather than hindrances, religious values can be strategically employed as assets in digital communications.